Actividades lúdicas para el desarrollo de habilidades socioemocionales en la Educación Inicial II - Moyano Torres, Heidy Alejandra (2025)
This paper presents the results of a study aimed at creating a recreational activities guide aimed at developing the social-emotional skills of students at the “Juan E. Verdezoto, Canton Babahoyo” Elementary School “Primary Education II”. The study was conducted using qualitative methods, collecting information through observations and interviews. There are a total of 60 children in early childhood education and 2 teachers, including a sample of 20 children, 10 from each class. A recreation guide was created to help teachers develop social-emotional skills through recreation. Through this study, it was possible to understand that recreational activities are necessary for the learning process because they facilitate the acquisition of social-emotional skills through interaction and cooperative play. Keywords: Methodological guide, recreational activities, social-emotional skills.